Is the GnRH Antagonist Protocol Effective at Preventing OHSS for Potentially High Responders Undergoing IVF/ICSI? - Weijie Xing; Haiyan Lin; Yu Li; Dongzi Yang; Wenjun Wang; Qingxue Zhang (PLoS ONE, 2015)
To determine if the GnRH antagonist protocol is effective in preventing ovarian hyperstimulation syndrome (OHSS) in potentially high responders.A total of 660 IVF-ET/ICSI cycles were retrospectively identified. The inclusion criterion was age ≤ 30 years. Cycles were divided into two groups: a GnRHa group and a GnRHant group. In the GnRHa group, the patients received one single injection of 1.0mg-1.3mg Triptorelin in previous mid-luteal phase. In the GnRHant group, a daily dose of 0.25 mg Cetrotide was initiated when a lead follicle obtained a mean diameter of 14 mm, continued up until the day of hCG administration. The duration of stimulation, total dose of Gn, implantation rate, pregnancy rate, and OHSS rate were compared.The duration of stimulation, E2 level on hCG day, numbers of oocytes retrieved, MII oocytes, and high-quality embryos in the GnRHa group were all significantly more than those in the GnRHant group. In the GnRHa group, 83.53% of cancelled fresh-transferred cycles were cancelled because of high risk of OHSS, which was significantly higher than that in the GnRHant group (43.55%, P<0.05). The incidence of OHSS in the GnRHa group was slightly higher than that in the GnRHant group. The implantation and clinical pregnancy rates in the GnRHa group were significantly higher than those in the GnRHant group (37.36% VS 19.25%, 62.78% VS 31.06%; P<0.05).Our study demonstrated that for potentially high responders, the GnRHant protocol can, to some extent, lower the cancellation and incidence rates of OHSS. The GnRHa protocol was superior to the GnRHant protocol in terms of implantation and clinical pregnancy rates.